Kondisi Sosial Ekonomi dan Modal Sosial pada Berbagai Tingkat Partisipasi Peserta Program Pos Pemberdayaan Keluarga (Kasus Posdaya Mandiri Terpadu, Desa Cikarawang, Kecamatan Dramaga, Kabupaten Bogor) - Suhaeri Mukti; Titik Sumarti (Jurnal Penyuluhan, 2013)
The purpose of this study are analyze the influence of socio-economic conditions and social capital on the level of program’sparticipation. The correlation level between of program’s participation are access to welfare benefits and economic benefits of thePosdaya Integrated Self. The research was conducted in the village of Cikarawang, District Dramaga. This study uses quantitativeand qualitative approaches. The results showed that the socio-economic conditions and social capital owned by the participantsrelated to the level of program participation program, and the level of participation in the program achieved the degree ofparticipation of tokenism Arnstein. Correlation test results demonstrate, there is a significant and strong correlation betweensocioeconomic conditions and social capital on the level of program participation. Other results show that the participationrate also has a significant and strong correlation with access to welfare benefits and economic benefits received by programparticipants.Keywords: Access to Welfare and Economic, Participation,Social Capital, Socio-Economic Condition